Pendidikan Finansial Hindu Dalam Sesonggan Bali - Putu Sanjaya (Purwadita : Jurnal Agama dan Budaya, 2021)
The welfare of human life today can not be separated from financial support. Simply put, whatever human needs today, need financial support in fulfilling them. There is almost nothing that can be obtained or realized for free. Therefore, good financial availability is a necessity that everyone should undoubtedly have. For Balinese people, in fact, their previous ancestors taught about financial education, which is contained in one of the Balinese proverbs called sesonggan. Keywords: Financial, Hindu, Bali